Impact of dietary Diversification on the nutritional status of children aged 0 to 59 months in the municipality of Tori-Bossito - Alohoutade, Parfait Segla; Avocefohoun, Alphonse Sako; Behanzin, Gbèssohele Justin; Kanazoe, Mohamed; Abdou Karim, Alassane Youssao; Chabi, Nicodeme; Baba-Moussa, Lamine Said (European Scientific Journal, ESJ, 2024)
In order to capitalize on the achievements for the sustainability of the NECDP (Nutrition and Early Childhood Development Project) in the municipality of Tori-Bossito, the impact of the Promotion of Food Diversification (PFD) on the nutritional status of children aged 0 to 59 months was evaluated. Anthropometric data (weight, height, age) in children aged 0 to 59 months and dietary data (consumption of salt with iodine, source of drinking water, the practice of hand washing, frequency and quality of meals served to children aged 6 to 59 months) was collected in the households of beneficiary women. This data was collected from 2019 to 2020 (considered as the period before PFD) and from 2021 to 2023 (considered as the period after PFD) through home visits, quarterly screening sessions, and monitoring and promotion of growth and stimulation and awakening of children from 0 to 23 months on a monthly basis. Significant differences through the analysis of variance were carried out at the 5% threshold according to the Student Newman-Keuls test. It showed from this study that after the PFD, a majority of households practice hand washing (85.12%), use a source of drinking water (80.39%), serve children more than three meals (58.3%) containing the three food groups (97.52%) per day but consumed poor salt in iodine in a proportion of 70.4%. The study also revealed that PFD significantly contributes to reducing the prevalence of all forms of malnutrition among children aged 6 to 59 months (from 3.52% to 1.59% for severely underweight, from 3.34% to 1.97% for severe wasting, and from 7.18% to 3.93% for severe stunting). On the other hand, PFD does not contribute to reducing the prevalence of severe underweight in children aged to 0 to 5 months (from 4.85% to 11.97%). The promotion of Food Diversification stands out as an important activity recommended for food and nutrition projects/programs in the fight against malnutrition in all its forms.